2016
DOI: 10.1177/0018726715624956
|View full text |Cite
|
Sign up to set email alerts
|

Binary logics and the discursive interpretation of organizational policy: Making meaning of sexual harassment policy

Abstract: Although workplace policies are written in neutral terms that give the appearance of rationality, research shows that policy meanings are in fact constructed and negotiated through discursive practices. Sexual harassment policies illustrate this phenomenon. Sexual harassment is a highly complex and fluid phenomenon that is dependent on context and culture for its meaning. Although sexual harassment policies tend to use language that appears to lie outside of the interpretive stream, these policies are in fact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 44 publications
3
40
0
6
Order By: Relevance
“…Additionally, given this study identified variation in managers' practice regardless of whether the organization had a strong diversity mandate, future research should empirically examine how organizations' (conflicting) diversity policies and activities produce and reproduce particular managerial ways of performing managing diversity. This is particularly pertinent in light of recent empirical research, demonstrating how “objective” organizational policies are interpreted in multiple ways in people's lived experience of them (Dougherty & Goldstein Hode, ).…”
Section: Implications For Managing Diversity Researchmentioning
confidence: 99%
“…Additionally, given this study identified variation in managers' practice regardless of whether the organization had a strong diversity mandate, future research should empirically examine how organizations' (conflicting) diversity policies and activities produce and reproduce particular managerial ways of performing managing diversity. This is particularly pertinent in light of recent empirical research, demonstrating how “objective” organizational policies are interpreted in multiple ways in people's lived experience of them (Dougherty & Goldstein Hode, ).…”
Section: Implications For Managing Diversity Researchmentioning
confidence: 99%
“…The construction of retirement as a period of entrepreneurial endeavour highlights how successful ageing has failed to resolve the issue of heterogeneity in later life. The construction does not treat the binary pairing of the success/decline discourses as neutral or morally equivalent (Dougherty & Hode, 2016). Rather it privileges a particular version of successful ageing (one where enterprise may be required) over earlier versions (where health and activity were sufficient markers) which are now aligned with decline.…”
Section: Discussionmentioning
confidence: 99%
“…These discourses of continued youthfulness and decline work together with consequences for individuals through the construction of identities that promote 'a particular view of what persons are and what they should be allowed to become ' (du Gay, 1996, p.3). Underpinning binary logics shape the structure by which meaning is produced and create subject positions which are linked to other hierarchical binary pairings such as young/old and male/female (Dougherty & Hode, 2016). Those positioned within the binary discourses of continued youthfulness and decline may find themselves targeted with new and problematic labels, particularly in relation to work.…”
Section: Later Life and The Binary Discourses Of Continued Youthfulnementioning
confidence: 99%
“…To combat this issue, organizations are attempting to minimize harassment in the workplace by creating anti-harassment policies (DOL, 201;Dougherty & Goldstein, 2016) and offering harassment training (Levin, 2016). While policies and trainings offer awareness of the functional definitions of workplace harassment, these strategies may prove inadequate for eradicating harassment in the workplace due to ambiguous definitions and confused perceptions of what qualifies as harassment (Branch, Ramsay & Barker, 2013;Gordon, Cohen, Grauer & Rogelbert, 2005;Pierucci, Echterhoff, Marchal, & Klein, 2014;Toker, 2016).…”
Section: Introductionmentioning
confidence: 99%